Cork based composites using polyolefin’s as matrix: Morphology and mechanical performance - Fernandes, Emanuel M.; Correlo, Vitor M.; a. M. Chagas, José; Mano, João F.; Reis, Rui L. (Composites Science and Technology, 2010)
The cork industry produces high amounts of cork powders resulting from the ﬁnal stages of cork processing or resulting from existing cork products. Usually these powders are burned and served to boilers in industrial processes. The main goal of this work is to transform this cork sub-product into a highly value composite product. The real value is dependent on the mechanical performance of this product. Thus the mixture between cork and thermoplastics, particularly the improvement of interfacial bonding, is an important topic, which needs to be developed. The interfacial afﬁnity can be greatly increased, applying superﬁcial modiﬁcation of one of the components, or by the use of coupling agents. In this work, a high amount of cork powder (50 wt.%) from different origins combined with different thermoplastic materials using melt based processes has been examined. Pultrusion was used to produce pellets and compression moulding to obtain boards to determine its properties. Coupling agents based on maleic anhydride (2 wt.%) improved the tensile strength successfully, while the cork powder has an a important role in the stiffness. The morphology of the surface fractures indicated a good dispersion of the cork and a good adhesion between both phases. Thermal properties of the composites disclosed a nucleating effect promoted by cork
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: cork and thermoplastic; Coupling agents; mechanical properties; Pultrusion; thermal properties